The use of online text based technologies as a medium for employee counselling: perceptions of online counsellors - Magogodi, Precious Priscilla Salamina (My University, 2017)
Technology is ubiquitous and presents an opportunity for the psychosocial profession to explore and expand the platforms through which counselling and support for employees is offered. The aim of the research study was to explore the perceptions of counsellors regarding the use of online text technologies as a medium for intervention in the workplace environment. Mobile technology globally and in South Africa is growing rapidly, people are connected to information and services more than ever before. More services are being offered and marketed through the use of online technology mediums; these include professional services for mental wellbeing counselling support. Recognising that this is a relatively new field of study, it is valuable to gain insight from experienced counsellors regarding the use of online text based technologies for counselling specifically for workplace environments. Cultural Historical Activity Theory (CHAT) is used as a framework that it explains how the object of study being text based counselling technologies are used currently characterised by highly mobile social media use. This study employed a qualitative approach and was contextualised to a specific organisation, the South African Depression and Anxiety Group (SADAG) because it offers online counselling interventions which include specific programmes for workplace environments on mental health. Purposive sampling was used to select a total of eight counsellors with experience using online text based mediums and two key informants representing management of the organisation. Individual face-to-face interviews were conducted using two semi- structured interview schedules. Thematic content analysis was used for interpretation of the data. The findings show that counsellors do not prefer to use text based online counselling technologies for serious mental health issues. Results indicate that though online text based technologies are relevant as part of employee wellness services in the workplace, the platforms are more suitable for containment, information and referral purposes. Recommendations from the study are for further research to inform standards of practise and formalised and structured training is required for counsellors.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Occupational Social Work, August 2017
Keywords: Employees--Counseling of--South Africa; Mental illness--South Africa; Mental illness--Treatment--South Africa; Technological innovations--South Africa